The Exploring University Students' Speaking Skills Through Think Pair Share Method in Online Learning - Sulastri Sulastri; Ratnawati Ratnawati; Mujahidah Mujahidah; St. Asriati. Am (Universitas Muhammadiyah Enrekang, 2023)
This quantitative research study analyzed the implementation of the TPS method on students' speaking skills. Twenty-seven students in the English education program at Universitas Muslim Indonesia participated in the study, which applied a speaking test and observation sheet to collect data on participants speaking skills. The study analyzed the implementation of TPS on students' speaking skills in terms of accuracy and fluency dealing with vocabulary and Grammar, as well as smoothness and self-confidence. The findings revealed that the use of the TPS method was able to improve students' speaking abilities. The result of the students' mean score in speaking accuracy in terms of vocabulary in cycle I was 6.85, and in cycle II, it was 7.97, which was improved by 1.12. Grammar in cycle I was 6.59; in cycle II, it was 7.73; it was improved to 1.14. Speaking fluency in terms of smoothness in cycle I was 7.10; cycle II was 8.22, it was improved to 1.12. Self-confidence in cycle I was 6.62, and cycle II was 8.54. It was improved to 1.92. The study concluded that the TPS method improved students' speaking skills of students. These findings contributed to understanding the potential benefits of the TPS method for improving students' speaking skills.